MARITIME TRANSPORTATION OF INDONESIAN POLICY - Hartanto Hartanto; Ong Argo Victoria; Anirut Chuasanga (Jurnal Pembaharuan Hukum, 2019)
In a period of 5 years (19.962 million) the number of shipping companies in Indonesia increased from 1,156 into 1,724 pieces, or increased 568 companies (an average increase of 10.5% pa). While the strength of the national shipping fleet enlarged, from 6.156 into 9.195 units (an average increase of 11.3% pa). But in terms of haulage capacity rose only slightly, namely from 6,654,753 into 7,715,438 DWT. Means the average capacity of the national shipping company declined. Throughout this period, the volume of sea trade grew 3% pa The volume of freight rose from 379,776,945 tonnes (1996) to 417,287,411 tonnes (2000), or an increase of 51,653,131 tons within five years, but not all of that growth can be met by the capacity of the national shipping company ( Indonesian-flagged vessels), even for domestic shipping (between ports in Indonesia). In 2000, the number of foreign ships which reached 1,777 units with a capacity of 5,122,307 DWT domestic load scooped by 17 million tonnes or about 31%.As a result, the Indonesian shipping industry is currently very poor. National shipping companies compete in national and international shipping market, due to weakness in all aspects, such as size, age, technology, and speed boats. In the field of international cargo (export / import) share of the national shipping company is only about 3% to 5%, with a declining trend (see Table below). These proportions are very unbalanced and unhealthy for the growth of the national shipping fleet strength.